Correction of Impacted Maxillary Permanent Anteriors - A Case Report - Varsha Sharma; Priti Shukla; Sushmita Pattnaik; Brahmananda Dutta (Indian Journal of Dental Research)
The maxillary anteriors play the most prominent role in an individual’s aesthetics, speech, and majorly psychology. The impaction of maxillary anterior teeth can be a challenging orthodontic problem that can be managed by interceptive orthodontics in early mixed dentition. In this particular case report, interceptive orthodontics alone may not bring desirable results because two problems need to be dealt simultaneously, namely, intraosseous crowding and midline shift due to impaction on the affected quadrant. In the article, a novel approach is being discussed, where aesthetics of the child was compromised due to impacted rotated maxillary anteriors that were exposed using soft tissue laser and allowed to erupt by selective removal of primary and permanent first premolar teeth on the affected side alone, leading to spontaneous alignment of arch discrepancy and relative correction of midline shift. A unilateral serial extraction sequence (D-4-C) would be effective treatment of choice. This approach adds psychological benefit to the child by using soft tissue lasers and unilateral serial extraction.